MOLECULAR IDENTIFICATION OF EXOTIC FRUIT FLY Bactrocera occipitalis (DIPTERA: TEPHRITIDAE) USING MITOCHONDRIAL CYTOCHROME OXIDASE I (COI) GENE - I Putu Sudiarta; Dwi Martiningsia; I Nyoman Wijaya (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2018)
Some of fruit flies have been reported as the important pest on fruits and vegetables in the world. Agricultural Quarantine Agency Denpasar reported that there was new coming species (exotic) of fruit flies in Bali in 2014 based on the morphological identification, namely Bactrocera occipitalis. However Bactrocera dorsalis complex have similar morphological characters and have a less distinctive character for taxonomic identification, therefore it is difficult to identify fruit flies accurately. Based on that phenomena, the accurate identification is needed. One of the more accurate identification techniques is based on molecular identification using DNA-based barcode. To identify fruit flies, DNA-based barcode using mitochondrial cytochrome oxidase I (COI) gene has been conducted. PCR analysis using Fruit Fly MT-CO1-F (FFMT-CO1-F) 5’-GGAGCATTAATYGGRGAYG-3’ as forward primer and HCO 5’-TAAACTTCAGGGTGACCAAAAATCA-3’ as reverse primer was successfully amplified around 600 bp of COI gene of fruit flies. Based on similarity of sequence product, the species was identifiedas Bactrocera occipitalis and same result was revealed using morphological identification. Phylogenetic analysis of B. occipitalis based on COI genes showed that B. occipitalis from Bali were in the same groups with Bactrocera species from Tarakan and Philippines. In addition, Bactrocera occipitalis as exotic fruit fly is a new report in Bali, Indonesia.